2018
DOI: 10.18805/ijare.a-4733
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic biofortification in rice varieties through zinc fertilization under aerobic condition

Abstract: A field experiment on agronomic biofortification in rice varieties through zinc fertilization under aerobic condition was carried out at Assam Agricultural University, Jorhat during autumn season of 2014. Among the Varities, Inglongkiri recorded significantly higher grain yield (21.09 q/ha) followed by Banglami (19.88 q/ha) under aerobic condition. Application of ZnSO4 @ 25 kg/ha + foliar spray @ 0.5% at 3 stages recorded the highest grain yield (21.46 q/ha) followed by application of ZnSO4 @ 25 kg/ha + seed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
3
10
0
Order By: Relevance
“…It might be due to favourable effect of zinc on the proliferation of roots and thereby increasing the uptake of plant nutrients from the soil supplying it to the aerial parts of the plant and ultimately enhancing the vegetative growth of plants. Similar findings also reported with (Barua and Saikia, 2018).…”
Section: Yield and Yield Attributessupporting
confidence: 91%
See 1 more Smart Citation
“…It might be due to favourable effect of zinc on the proliferation of roots and thereby increasing the uptake of plant nutrients from the soil supplying it to the aerial parts of the plant and ultimately enhancing the vegetative growth of plants. Similar findings also reported with (Barua and Saikia, 2018).…”
Section: Yield and Yield Attributessupporting
confidence: 91%
“…Zinc and Iron plays major role in biosynthesis of Indole acetic acid(IAA) and especially due to its role in initiation of primodial reproductive parts and partitioning of photosynthates towards them which promotes yield (Barua and Saikia, 2018). Further, higher Harvest Index (46.70%) was recorded with 15 days old seedlings and foliar application of iron at 45 DAT.…”
Section: Yield and Yield Attributesmentioning
confidence: 99%
“…(Jat et al 2011) [8] also obtained higher grain weight of rice by combined application of zinc and iron. These findings are in accordance with (Angelin et al 2017) [16] and (Barua and Saikia 2018) [1] . T1: Absolute control, T2: RDF, T3: RDF + SA of ZnSO4 @ 25 kg ha -1 , T4: RDF + 2 FS of 0.5% ZnSO4 at 25 Zinc uptake (kg ha -1 ) in grain and straw indicates that different treatments shows marked variation on Zinc uptake in grain and straw (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Foliar spray of 0.5% and 1.0% ZnSO4 increased grain yield by 10 and 18.8%, respectively while its soil application at the rate of 5, 10 and 15 kg ha -1 increased grain yield by 18, 32 and 41%, respectively over the control. Ghoneim (2016) [14,15] Barua and Saikia (2018) [7] revealed that significant variations in yield attributing characters were recorded due to different zinc fertilization. Plots receiving ZnSO4 @ 25 kg/ha as basal + 0.5% foliar application produced significantly higher number of effective tillers/meter, more number of grains/panicle and length of panicle than that of other zinc fertilization treatments.…”
Section: Need Of Biofortification In Ricementioning
confidence: 99%